1996
DOI: 10.1021/jp960538k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alkyl Chain Structure on Carbon−Halogen Bond Dissociation and β-Hydride Elimination by Alkyl Halides on a Cu(100) Surface

Abstract: The effects of alkyl chain structure on the rate of carbon−halogen bond scission in alkyl chlorides, bromides, and iodides on a Cu(100) surface and on the rates of β-hydride elimination by the alkyl products of these carbon−halogen bond scission reactions have been studied under ultra-high-vacuum conditions. It is found that the carbon−halogen bond dissociation rates increase in the order:  C−Cl < C−Br < C−I and C(1°)−X < C(2°)−X < C(3°)−X, where X denotes the halogen and 1°, 2°, 3° refer to the number of alky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 59 publications
6
54
1
Order By: Relevance
“…Furthermore, ICH 2 CH 2 OH decomposes, via C-I scission, on Ni(1 0 0) at 150 K [6]. On Cu(1 1 1) and Cu(1 0 0) surfaces, the C-I bonds of C 2 H 5 I and the iodides with longer carbon chains dissociate below 120 K [15,16].…”
Section: Desorption and Reactions Of Ich 2 Ch 2 Oh On Cu(1 0 0)mentioning
confidence: 99%
“…Furthermore, ICH 2 CH 2 OH decomposes, via C-I scission, on Ni(1 0 0) at 150 K [6]. On Cu(1 1 1) and Cu(1 0 0) surfaces, the C-I bonds of C 2 H 5 I and the iodides with longer carbon chains dissociate below 120 K [15,16].…”
Section: Desorption and Reactions Of Ich 2 Ch 2 Oh On Cu(1 0 0)mentioning
confidence: 99%
“…Most commonly, this problem has been surmounted by using thermal, photochemical or electron induced dissociation (EID) of ethyl halides (C 2 H 5 X, X = Cl, Br, I) adsorbed at low temperatures on metal single crystals [3,4]. In this manner, studies of ethyl chemistry have been reported on copper [5][6][7][8][9], silver [10,11], nickel [12,13], platinum [14][15][16][17], and rhodium [18]. A disadvantage of this approach is the introduction of coadsorbed halogen adatoms on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Additional work using alkyl groups with constrained structures, cyclic compounds in particular, have been employed to point to the planar nature of the transition state [44]. Selectivity towards the abstraction of hydrogens from inner carbons has also been reported [34,41]. All these characteristics parallel the behavior reported on discrete organometallic compounds.…”
Section: B-hydride Eliminationsmentioning
confidence: 92%
“…For instance, the CH 3 symmetric stretching (around 2965-2963 cm )1 ) and deformation (1366 and 1390-1395 cm )1 ) modes in normal and neopentyl-a-d 2 become narrower and split upon scission of the CAI bond, and the CD 2 deformation in both a-d 2 and perdeuterio isotopomers shifts down (from 927-917 to 918-902 cm )1 ). Typically, most CAI or CABr bonds in halohydrocarbons on late transition metals cleave below 200 K, and display activation barriers on the order of 5 kcal mol )1 [33,34]. The preparation of surface species, alkyls in particular, via oxidative addition of appropriate halohydrocarbon precursors has allowed us to characterize the surface chemistry of hydrocarbon conversion catalysis in great detail [19,21,23].…”
Section: Oxidative Additionsmentioning
confidence: 99%
See 1 more Smart Citation